Carbon Accounting: Challenges for Research in Management Control and Performance Measurement. (December 2013) - Hartmann, Frank; Perego, Paolo; Young, Anna
<x xml:space="preserve">Abstract</x> Carbon reduction programs and corporate emissions reporting have expanded rapidly across firms in response to climate change and global warming. This development is partly driven by institutional demands and partly by value creation considerations. The consequences of these developments for management accounting and control (MAC) are not clear, despite anecdotal evidence that suggests an increasing effort to incorporate carbon accounting into traditional decision and reporting processes. The reasons for this lack of clarity are the disproportionate focus in practice on carbon disclosure, compared to a small number of empirical studies, and the absence of an academic debate in this novel area from a MAC perspective. This paper seeks to stimulate such an academic debate by reviewing the extant literature, identifying key theoretical and empirical shortcomings of extant academic research, and outlining some directions for future studies on carbon accounting. These directions are inspired by more established MAC research that may help to guide and organize MAC research in the emerging and exciting field of carbon accounting.